Customer concentration and firm risk: The role of outside directors from a major customer - Kim, Taeyeon; Kim, Hyun-Dong; Park, Kwangwoo (Journal of Banking & Finance, 2023)
This paper examines the role of customer-affiliated outside directors on suppliers in reducing risk arising from having a major customer. Using a sample of US supplier firms, we find that a positive relationship between having a major customer and supplier risk is weakened with the presence of the major customer's representatives at suppliers' board. We further show that suppliers with customer-affiliated outside directors are more likely to have less conservative financial policies. Our results suggest that customers' board membership at suppliers helps mitigate the business risk due to the tightened supplier–customer relationship and reduced information asymmetry.